Ischemic Gastropathic Ulcer Mimics Gastric Cancer - Saleh Daher; Ziv Lahav; Ayman Abu Rmeileh; Meir Mizrahi; Tawfik Khoury (Case Reports in Gastrointestinal Medicine)
Gastric ulcer due to mesenteric ischemia is a rare clinical finding. As a result, few reports of ischemic gastric ulcers have been reported in the literature. The diagnosis of ischemic gastropathy is seldom considered in patients presenting with abdominal pain and gastric ulcers. In this case report, we describe a patient with increasing abdominal pain, weight loss, and gastric ulcers, who underwent extensive medical evaluation and whose symptoms were resistant to medical interventions. Finally he was diagnosed with chronic mesenteric ischemia, and his clinical and endoscopic abnormalities resolved after surgical revascularization of both the superior mesenteric artery and the celiac trunk.